Strategic Leadership in Islamic Boarding School Development (A Study at Al-Qur’an Nur Medina Boarding School, South Tangerang) - Utama, Rony Edward; Rosyada, Dede; Andry Priharta; Masyitoh, Masyitoh; Bahri, Saiful (Technium Social Sciences Journal, 2023)
The purpose of the study is to obtain a strategic leadership model at the Al-Qur’an Nur Medina Islamic Boarding School. This study uses an interpretive paradigm with a phenomenological qualitative approach. Data collection techniques were carried out by interviews, documentation studies, and observation, while data analysis were from data analysis and interpretation with theoretical validation through data and method triangulation. The results of the study show that, first, the implementation of the vision and mission of the Islamic boarding school development program has empowered its network and resources; second, the development of human resources has been carried out through a process of observation, selection, training, placement, guidance and control of personnel, curriculum, and learning processes that are carried out according to their competence and sustainable regeneration; third, financial resources rely on zakat (obligatory charity), infaq (gift of money), shadaqah (alms) and donations, with integrated, accountable and transparent financial administration governance; fourth, the development of infrastructure facilities by taking into account the priority scale; and fifth, the implementation of an operational control system under the control of the head of Islamic boarding school by conducting interpersonal coordination.